Elucidating perceived overall service quality in retail banking. Issue 5 (3rd July 2017) - Hamzah, Zalfa Laili; Lee, Siew Peng; Moghavvemi, Sedigheh
Abstract : Purpose: The purpose of this paper is to examine the dimensions of service quality (SERVQUAL) from the perspective of the customers and its relationships with perceived overall SERVQUAL in retail banking and also investigate the relationships between perceived overall SERVQUAL and customer trust, customer satisfaction, and bank reputation. Design/methodology/approach: A survey questionnaire was constructed, and data were collected from 375 regular customers of local banks. The convenience sampling method was employed to collect data from existing customers of local banks operating in the Klang Valley area of Malaysia. Structural equation modelling was applied to analyse the data. Findings: The results of the study indicate four key dimensions of SERVQUAL – tangibles, empathy, reliability and security, and internet banking – all of which are significantly and positively related to customers' perceived overall SERVQUAL. Internet banking facilities are another significant determinant of the perceived overall SERVQUAL. The results are indicative of the strong and positive effect upon customer satisfaction, their trust in the bank, and, finally, a bank's reputation. Research limitations/implications: This study has presented and tested empirical study of perceived overall SERVQUAL model in the banking industry, particularly in the Malaysian context. This research identified the dimensions of SERVQUAL (i.e. tangibles, empathy, reliability and security, and internet banking) that influence the overall perceived SERVQUAL, and how these overall perceptions will eventually influence customer trust, customer satisfaction, and bank reputation is valid and reliable in retail banking industry. This study, however, only focussed on the banking industry. Given the diversity of the service industry, these findings may have to be tested for the applicability to different service industries in future studies. Practical implications: This research is useful to bank managers as it helps them improve SERVQUAL to protect and expand their respective market share in a highly competitive industry. Banks could utilise the results of this study to improve their service tangibility, empathy, reliability, and security, which will affect both customer trust and satisfaction, and enhance a bank's reputation. Social implications: The findings of specific dimensions of SERVQUAL will contribute to customer perception of banks' image and reputation, and strengthen trust and satisfaction. Moreover, assisting customers towards the understanding of how they should received high quality of services with regard to quality should be perceived as emphatic, reliable, secured and tangibility of service. Originality/value: The findings of this study highlight the specific dimensionalities of SERVQUAL in influencing the perceived overall SERVQUAL. This study will increase the understanding on the impact of perceived overall SERVQUAL on consumer trust, customer satisfaction, and a bank's reputation. Specifically, it reports an empirical study of a model of perceived overall SERVQUAL that simultaneously considers the direct effects of perceived overall SERVQUAL on customer trust, customer satisfaction and bank reputation.